Black hole attack behavioral analysis general network scalability - Layth A. Khalil Al Dulaimi; R. Badlishah Ahmad; Naimah Yaakob; Mohd Hafiz Yusoff; Mohamed Elshaikh (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
A mobile ad hoc network (MANET) is a frameworkless system of different mobile devices known for its self-arranging conduct. MANETs can convey over moderately data transfer capacity compelled routing connections. In a blackhole assault, a malicious node falsely advertises the shortest path to the destination node, intending to disrupt communication. Our objective was to review the impact of a blackhole assault on networks. To accomplish this, we simulated MANET situations, which include the blackhole node, using the OMNET++ simulator to demonstrate the effects of a single blackhole attack and multiple blackhole attacks on MANET performance have examined for networks. We analysed MANET performance under blackhole assaults through the use of performance grids. A mobile ad hoc network (MANET) is a frameworkless system of different mobile devices known for its self-arranging conduct. MANETs can convey over moderately data transfer capacity compelled routing connections. In a blackhole assault, a malicious node falsely advertises the shortest path to the destination node, intending to disrupt communication. Our objective was to review the impact of a blackhole assault on networks. To accomplish this, we simulated MANET situations, which include the blackhole node, using the OMNET++ simulator to demonstrate the effects of a single blackhole attack and multiple blackhole attacks on MANET performance have examined for networks. We analysed MANET performance under blackhole assaults through the use of performance grids..